Pengaruh Pajak,Tax Havens,Exchange Rate, dan Tunneling Incentive Terhadaptransfer Pricing pada Perusahaan Multinasional - Fitriyani Samalagi; Asrudin Hormati; Iqbal M. Aris Ali (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to determine the direct and indirect influence of taxes, tax havens, exchange rates and tunneling incentives on transfer pricing in multinational companies listed on the Indonesian Stock Exchange (IDX) for the 2018-2022 period. This research uses quantitative methods using secondary data. This research uses quantitative methods using secondary data. This research uses quantitative methods using secondary data. The results of hypothesis testing in this research show that taxes, tax havens¸exchange rates do not have a positive effect on transfer pricing, tunneling incentives have a positive and significant effect on transfer pricing in multinational companies.